Insulin oedema in type 2 diabetes mellitus: a case report - Md Aris, Mohd Aznan; Tan, Kui Foung; Said, Abdul Hadi (Academy of Family Physicians of Malaysia, 2022)
Insulin oedema is a rare condition that may occur after the initiation or rapid intensification of insulin therapy in patients with long-standing hyperglycaemia, commonly with type 1 diabetes mellitus (DM). We reported a case of insulin oedema in a patient with type 2 DM who presented with swelling of the extremities and weight gain of 3 kg 1 week after insulin initiation. A course of furosemide was administered, but no significant immediate improvement was observed; however, the lower limb swelling resolved spontaneously after 3 months of follow-up. The patient also achieved adequate diabetic control with insulin, as shown by the reduction of her HbA1c from 10.7% to 6.9% over 6 months. Insulin oedema is a diagnosis of exclusion after ruling out other differential diagnoses, such as cardiac, renal, or liver failure. Although insulin oedema carries with it a good prognosis, physicians should be aware of the condition to avoid misdiagnosis.